Analisis Kepuasan Mahasiswa Universitas Muhammadiyah Ponorogo terhadap SIMTIK Menggunakan Metode End User Computing Satisfaction (EUCS) - Fajar Tri Widodo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Advances in information technology have penetrated several aspects of human activities, including educational activities. Muhammadiyah University of Ponorogo, a campus that has implemented technology, has developed a website to make lecture activities easier, especially for taking attendance, checking schedules, checking financial billing data, and viewing grades. A good website must make it easy for users to use it. Ease of use of the website will also give a good impression from users. In this research, the author conducted research to conduct an analysis of student satisfaction at Muhammadiyah University of Ponorogo towards the SIMTIK website. The method used in this research is the End User Computing Satisfaction (EUCS) method. The population in this study were active students at Muhammadiyah University of Ponorogo, totaling 31 students. Data was obtained from a questionnaire that the author distributed via Google Form. The data that has been obtained is processed using SPSS software and statistically processed using a Likert scale. To measure the level of satisfaction, we also use a Likert scale satisfaction table. The results of each dimension are, the Content dimension has an average value of 3.87 (satisfied), the Format dimension has an average of 3.17 (quite satisfied), the Timeliness dimension 3.53 (satisfied), the Ease of Use 2.6 (quite satisfied), and Accuracy (quite satisfied). From these five dimensions, an average of 3.25 was obtained and was included in the quite satisfied category.